Polymers with carbon fillers for powerful resistors - Natalia Nikolaevna Minakova; Vasily Yakovlevich Ushakov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
Wide use of resistors in electric power industry, electrical engineering, powerful-pulsed power engineering (Pulsed Power) makes the development of the recipe and technology for producing resistive materials and products based on them very relevant. These products would meet high requirements not only for performance characteristics, but also for minimizing material and energy consumption, processibility and, as a result, the maximum possible reduction in value. The main aim of the study is further improvement of the method developed by the authors for selecting resistive polymeric composite material. This method takes into account, on the one hand, the effect of various operating factors on the material, and, on the other hand, it does not increase the cost of raw materials and technique of manufacturing finished products from them. High-resistance metals and composite materials on a ceramic base, used for these purposes for many decades, are made from expensive materials using sophisticated technology. Some decades ago, the polymeric materials with electrically conductive fillers attracted the attention of scientists and technologists. Experience has shown that for a combination of properties, electrical products made of such materials are suitable for use as resistors, antistatic, shielding, and grounding devices, heaters, etc. Their large-scale production and use are restrained by the complexity of selecting components of the composite material that provides the required consumer properties. The methods: textural and fractal analysis using specially designed fractal packets; direct measurement of bulk resistance - the most important parameter for most products; electron microscopy; X-ray diffraction and thermal analyzes; regression and correlation analyzes. The results. The authors proposed the use of macrostructure textural pattern with subsequent comparison of materials with the known and unknown properties. Approbation of the proposed method on real composite materials showed rather high reliability of the results obtained with its help.